2016
DOI: 10.1099/jgv.0.000354
|View full text |Cite
|
Sign up to set email alerts
|

Marek's disease virus undergoes complete morphogenesis after reactivation in a T-lymphoblastoid cell line transformed by recombinant fluorescent marker virus

Abstract: T-lymphocytes are central targets of Marek's disease, a major chicken disease induced by the oncogenic alphaherpesvirus Marek's disease virus (MDV). T-lymphocyte infection is also associated with immunosuppression and virus latency. To decipher viral morphogenesis in T-lymphocytes, we used the recombinant vRB-1B 47EGFP marker virus to generate a new lymphoblastoid cell line, 3867K, that exhibited typical properties of other MDV-transformed chicken cell lines in term of cell markers, reactivation rate and infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…However, we found that a small proportion of cells spontaneously expressed EGFP at levels similar to those of MDV lytic genes such as pp38 seen in cells with reactivating virus [ 22, 29 ]. We have also recently shown that these cells produce virus particles [ 28 ]. The ability to isolate these spontaneously reactivating fluorescent cells presented an ideal resource to analyse, with minimal manipulation, cell populations showing viral reactivation in relation to the majority latent cell population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we found that a small proportion of cells spontaneously expressed EGFP at levels similar to those of MDV lytic genes such as pp38 seen in cells with reactivating virus [ 22, 29 ]. We have also recently shown that these cells produce virus particles [ 28 ]. The ability to isolate these spontaneously reactivating fluorescent cells presented an ideal resource to analyse, with minimal manipulation, cell populations showing viral reactivation in relation to the majority latent cell population.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we established two LCLs from tumours induced by pRB1B-UL47eGFP virus [ 27 ] as a tool to study spontaneous lytic switch of MDV. We have recently used transmission electron microscopy to demonstrate morphogenesis of herpesvirus particles in the enhanced green fluorescent protein (EGFP)-expressing cells of one of these cell lines [ 28 ]. Global gene expression profiling using RNA-seq was used to examine the transcriptome changes associated with lytic switch.…”
Section: Introductionmentioning
confidence: 99%
“…Primary chicken embryonic skin cells (CESCs) were prepared from 12-day-old specific-pathogen-free (SPF) White Leghorn (LD1) chicken embryos and maintained in culture as previously described (48). The MDCC-3867K cell line was derived from a renal lymphoma induced upon infection of a chicken with the highly pathogenic recombinant vRB-1B 47EGFP virus encoding the UL47 gene fused to the enhanced green fluorescent protein (EGFP) (47). 3867K cells were cultured in RPMI 1640 supplemented with 2 mM glutamine, 1% pyruvate, 1% nonessential amino acids, 1% glucose, 10% tryptose phosphate broth, and 10% fetal bovine serum (FBS) and maintained at 41°C in a 5% CO 2 atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…Next, we set out to determine if DNA damage is induced upon MDV reactivation. We used a lymphoblastoid cell line that expresses GFP fused to the tegument protein UL47 upon reactivation (3867K cells), as described previously (47). We sorted EGFP-positive and -negative cells and assessed DNA damage by comet assays.…”
Section: Fig 2 Dna Damage Induction Enhances MDV Replication (A To D)mentioning
confidence: 99%
“…Spleen samples were collected from all infected groups at 20 th , 25 th , 30 th , 35 th , and 40 th weeks post-infection from different groups and tested by PCR assay for the detection of MDV [ 18 ]. Furthermore, at 40 th week post-infection, tumorized spleen sample of Bovans breed was collected and prepared for examination by transmission electron microscope (TEM) to confirm the presence of MDV [ 19 ].…”
Section: Methodsmentioning
confidence: 99%